2017
DOI: 10.2134/agronj2016.05.0275
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Climate Change and Adaptation on Maize in Northeast China

Abstract: Northeast China (NEC) is an important region for maize (Zea mays L.) production in China, and is the country's most signifi cant commercial food base. However, NEC is also one of the areas that are most signifi cantly aff ected by climate change in this country. Maize is sensitive to climatic changes, and to develop eff ective strategies for guaranteeing regional food security, it is essential to understand the mechanisms of the impacts of climate change and the eff ectiveness of adaptation measures in NEC. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 46 publications
7
36
0
2
Order By: Relevance
“…At the same time, future maize yields in regions V-VI would decrease as a result of the decline in precipitation and solar radiation due to warming temperatures accelerating growth phases. These findings are consistent with the results of previous studies in all maize planting regions except Northwest China, where other studies found that future maize yields would decrease (Xiong et al 2007, Tao and Zhang 2011, Kang et al 2014, Lin et al 2017, Liang et al 2018. This inconsistency is possibly Figure 5.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, future maize yields in regions V-VI would decrease as a result of the decline in precipitation and solar radiation due to warming temperatures accelerating growth phases. These findings are consistent with the results of previous studies in all maize planting regions except Northwest China, where other studies found that future maize yields would decrease (Xiong et al 2007, Tao and Zhang 2011, Kang et al 2014, Lin et al 2017, Liang et al 2018. This inconsistency is possibly Figure 5.…”
Section: Discussionsupporting
confidence: 92%
“…They also reported that by combining cultivar and the best planting date, they simulated an increase in production by 15%. Similarly, a study in Northern China by Lin et al (2017) showed that maize yields would decrease by 6.9% and increase by 15.9% if planting days were advanced or delayed by 15 days respectively. Another notable example is by Parent et al (2018) who, in their study using APSIM model and six field experiments in South and Northern Europe projected an increase of 4% -7% in grain production through adaptation that involves genetic variability of flowering during the crop cycle.…”
Section: Adaptation Strategies and Their Implicationsmentioning
confidence: 91%
“…The major adaptation strategies suggested for consideration on crop models include breeding new cultivars, proper irrigation and soil nutrient management (Bannayan, Paymard, & Ashraf, 2016;Lin et al, 2017;Moradi, Koocheki, Mahallati, & Mansoori, 2013;Rurinda et al, 2015;.…”
Section: Adaptation Strategies and Their Implicationsmentioning
confidence: 99%
See 2 more Smart Citations